LINGUISTIC STYLE IN AS-SHAMTU: A STYLISTIC ANALYSIS OF IMAM AS-SYAFI’I’S POETIC EXPRESSION - Mafatihatul Maqhfiroh; Ulil Absar; Salman AlFarisi; Nur Mutmainnah (Afshaha: Jurnal Bahasa dan Sastra Arab, 2026)
This study is motivated by the importance of a comprehensive linguistic analysis of classical Arabic literary works to uncover their aesthetic and intellectual dimensions. The poem As-Shamtu by Imam Asy-Syafi‘i holds significant moral and rhetorical value, yet it has rarely been examined through a multi-level linguistic framework. This research aims to analyze the poem through five linguistic levels: phonology, morphology, syntax, semantics, and stylistics. This study employs a qualitative method with a descriptive analytical approach based on library research. The data consist of the text of As-Shamtu, collected through documentation techniques and analyzed using content analysis, including identification, classification, interpretation, and conclusion drawing according to the five levels of analysis. The findings reveal that, phonologically, the poem employs baḥr tawil with taf’ilah patterns that undergo zihaf and ʿillah, along with a consistent rhyme scheme that produces a harmonious rhythm. Morphologically, the dominance of fiʿl madhi, mashdar, and ism faʿil strengthens the density of meaning. Syntactically, the combination of verbal and nominal sentences creates a cohesive structure. Semantically and stylistically, “silence” is constructed as a symbol of wisdom through devices such as istiʿarah, tashbih baligh, kinayah, tafdil, and tauriyah, affirming the poem’s contemplative and social values.